Inovasi E-Bussines Website “SIKOMPIT” sebagai Kolaborasi Proyek dan Peluang Karier Talenta IT - Novia Ramadhani; Puput Nur Fadilah; Damayanti, Arifa; Prasasti Karunia Farista Ananto (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
The gap between IT graduates’ skills and industry demands remains a barrier in the digital workforce. Limited project experience and professional connections hinder young talent from entering the job market. SIKOMPIT is introduced as an innovative solution a digital business platform that bridges collaboration between students, graduates, and industry partners. The development adopts a user-centered design approach through stages such as user research, backlog creation, roadmap planning, and business strategy using BMC, OKRs, and Product Metrics. Product validation was conducted through prototyping, usability testing, and A/B testing. Results show that SIKOMPIT has the potential to improve job readiness, project portfolios, and professional connectivity. The platform also contributes to building a collaborative digital ecosystem that supports the development of tech human resources in Indonesia.